Professional obligations and the demandingness of acting against one’s conscience - Giubilini, A (BMJ Publishing Group, 2024)
Conscience is typically invoked in healthcare to defend a right to conscientious objection, that is the refusal by healthcare professionals to perform certain activities in the name of personal moral or religious views. On this view, freedom of conscience should be respected when the individual is operating in a professional capacity. Others would argue, however, that a conscientious professional is one that can set aside one’s own moral or religious views when they conflict with professional obligations. The debate on conscientious objection has by and large crystallized around these two positions, with compromise positions aiming at striking a balance between the two, for instance by arguing for referral requirements by objecting healthcare professionals. In this article I suggest that the debate on conscientious objection in healthcare could benefit from being reframed as a problem around demandingness rather than one about freedom of conscience and moral integrity. Being a professional, and a healthcare professional specifically, typically requires taking on additional burdens compared to non-professionals. For instance, healthcare professionals are expected to take on themselves higher risks than the rest of the population. However, it is also widely agreed that there are limits to the additional risks and burdens that healthcare professionals should be expected to take on themselves. Thus, a question worth exploring is whether, among the extra burdens that healthcare professionals should be expected take on themselves as a matter of professional obligation, there is the burden of acting against one’s own conscience.